Ethnoecology of Communication of Fatumnasi Community and Mount Mutis - Nara, Maria Yulita; Jelahut, Felisianus Efrem; Swan, Maria V.D.P; Noya Letuna, Mariana Agusta (International Journal on Social Science, Economics and Art, 2025)
The purpose of this study is to determine how the Ethnoecology of Mount Mutis communication with the Fatumnasi Community as one of the community groups that live and 'coexist' with Mount Mutis. The method used in this study is Qualitative using a case study approach. The results of this study are that the Fatumnasi community views Mount Mutis as a source of life and a mother who breastfeeds most of the island of Timor. This view and belief are benchmarks for the community to continue to maintain and respect the existence of Mount Mutis by performing various rituals and implementing various prohibitions through the government and customs, thus proving that the Fatumnasi community is able to build environmental communication or combine ethnology and ecology which is evident in communication in the form of community responses to the existence of Mount Mutis.